Experimental and numerical study of MILD combustion in a bench-scale natural gas partial oxidation gasifier. (1st April 2017) - Li, Xinyu; Dai, Zhenghua; Guo, Qinghua; Liang, Qinfeng; Wang, Fuchen
Highlights: MILD combustion is studied in a natural gas partial oxidation gasifier. MILD combustion is achieved in an inverse diffusion configuration. MILD combustion is established due to the dilution of oxygen before ignition. A barrier stream between oxygen and syngas is necessary for realizing MILD combustion in gasifiers. Abstract: Moderate and intense low-oxygen dilution (MILD) is a promising combustion technology for the non-catalytic partial oxidation (POX) process of natural gas. This study investigates the establishment of MILD combustion in a bench-scale non-catalytic partial oxidation gasifier. Experiments under both inverse diffusion configuration (IDC) and normal diffusion configuration (NDC) are carried out using methane and pure oxygen as reactants. The flame appearances and temperature profiles are recorded using an imaging system and thermocouples, respectively. Results show that no visible flame can be observed in IDC case while a flame can be observed near the burner exit in NDC case. The effects of jet velocity and O2 /CH4 ratio on the IDC flame are further studied. Numerical simulations of the experimental cases are also performed and the results agree well with the experimental results. It is found that the recirculation rate inside the furnace is sufficiently high to fully dilute the reactants. Combustion regime classification on grid scale shows that MILD combustion is established in the gasifier in IDC case. Analysis on the flame structure in IDC case shows that dilution of oxygen before ignition is the reason for the establishment of MILD combustion and the barrier effect of fuel between oxygen and hot syngas in the necessary condition for this process.